Implementing smoking bans in American hospitals: results of a national survey. Issue 1 (1st March 1998) - Longo, Daniel R; Feldman, Mary M; Kruse, Robin L; Brownson, Ross C; Petroski, Gregory F; Hewett, John E
Abstract : OBJECTIVES: To determine how well hospitals complied with the Joint Commission on Accreditation of Healthcare Organizations (JCAHO) tobacco control standards, which required banning smoking in hospital buildings; to explore issues involved in developing and implementing smoking bans; and to ascertain the perceived success of the policies. DESIGN: Postal survey conducted January through June 1994. PARTICIPANTS: Stratified random sample of American hospitals surveyed by JCAHO (n = 1055). MAIN OUTCOME MEASURES: Enacting smoking policies more restrictive than the JCAHO standard; the respondent's judgment of the relative success of the hospital's smoking policy. RESULTS: More than 96% of hospitals complied with the smoking ban standard; 41.4% enacted policies that were more restrictive than required by JCAHO. Several characteristics were associated with exceeding JCAHO requirements: location in a "non-tobacco state"; having fewer than 100 beds; location in a metropolitan statistical area; having unionised employees; and having no psychiatric or substance abuse unit, favour having the same tobacco policy in psychiatry and substance abuse units as the rest of the hospital. More than 95% of respondents viewed their hospital's policy as successful. The JCAHO requirements and concern for employees' health were the major forces influencing hospitals to go smoke-free. Negative employee morale and lack of acceptance by visitors and patients were the most commonly cited barriers to overcome when implementing smoke-free policies. CONCLUSIONS: Smoking bans were successfully implemented in American hospitals, with many restricting smoking beyond the JCAHO standard. Other industries wishing to follow hospitals' lead would be most likely to succeed in the context of a social norm favouring a smoking ban and regulation by an outside agency.